Assessing neonatal nurses: transitioning preterm infants to oral feeding - a multicenter cross-sectional study - Abdelaziz Hendy; Yasmine M. Osman; Hanan F. Alharbi; Maha Suwailem Shuaib Alshammari; Mohammed Musaed Ahmed Al-Jabri; Naif S. Alzahrani; Ahmed Hendy; Abdulaziz Mofdy Almarwani (BMC Nursing)
Abstract Background In Egypt, approximately 10% of preterm deliveries occur between 32 and fewer than 37 weeks, leading to high neonatal intensive care unit (NICU) admissions. Preterm infants often face oral feeding difficulties due to immature development, which can lead to extended hospital stays and increased health risks. Aim To assess neonatal nurses’ performance in terms of the transition to oral feeding in preterm infants, focusing on knowledge, practices, and attitudes. Methods A descriptive, quantitative, multicenter, cross-sectional study was conducted across 16 hospitals in five governorates in Egypt from November 2023 to March 2024 involving 553 neonatal nurses. The data were collected through a self-administered questionnaire assessing knowledge and attitudes and through an observed checklist for nurses’ practices. The study used statistical methods, including binary logistic regression, to analyze the data. Results The findings revealed significant knowledge gaps among nurses, particularly in terms of oro-motor function, suck-swallow-breathe patterns, and nonnutritive sucking. A total of 64.6% of the nurses had unsatisfactory knowledge, 58.6% had unsatisfactory practices, and 45% had a negative attitude toward the oral feeding transition. Key predictors of satisfactory practices included higher education levels, full-time employment, and positive attitudes. Conclusion This study highlights critical gaps in neonatal nurses’ knowledge and practices regarding the transition to oral feeding in preterm infants. Addressing these gaps through targeted educational interventions and ongoing support is essential for improving care quality and outcomes for infants. The findings revealed that a substantial proportion of nurses lacked adequate knowledge of critical areas, such as oro-motor function, the suck-swallow-breathe pattern, and nonnutritive sucking. These knowledge deficits could hinder the ability of nurses to provide optimal care during this crucial transition.